Multifaceted - Fundaro, Daniela (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2023)
This poem reflects on the author's experience of wearing different "hats" or roles in their life - as an artist, a teacher, and a combination of the two. While they find fulfillment in their artistic pursuits and personal introspection, their role as a teacher comes with bureaucratic responsibilities that can be overwhelming. However, they see the value in combining their artistic and teaching skills to inspire their students and create a sense of community. The poem ultimately highlights the importance of self-reflection and how our experiences and interactions with others shape our identity.